Influenza C virus infection in military recruits—symptoms and clinical manifestation. Issue 5 (30th September 2013) - Kauppila, Jaana; Rönkkö, Esa; Juvonen, Raija; Saukkoriipi, Annika; Saikku, Pekka; Bloigu, Aini; Vainio, Olli; Ziegler, Thedi
Abstract Due to the lack of rapid diagnostic tests, clinical features of Influenza C virus infections are poorly characterized. Respiratory infections in military recruits in eastern Finland were monitored between July 2004 and December 2005 in order to study the epidemiology and clinical picture of infections caused by this virus. Blood samples were obtained at entry and at the end of the military service, and during each episode of respiratory infection to measure antibody responses against 10 viral and 2 bacterial pathogens. If possible, sputum samples were collected during the acute phase of respiratory infection episodes. Symptoms of the episodes were recorded for comparison of the clinical picture caused by various infectious agents. Infection with influenza C virus was detected in 38 of 892 young men during their service. The virus usually caused a mild upper respiratory tract infection. Most typical clinical features of influenza C virus infection were cough, rhinitis, and hoarseness. A striking difference to infections caused by influenza A virus was the lack of fever. Influenza C virus is an important cause of a respiratory tract infection in army conscripts. Infections with this virus are usually mild but can be complicated in some cases. J. Med. Virol. 86:879–885, 2014. © 2013 Wiley Periodicals, Inc.